Pengetahuan Etnosains Guru Biologi di SMA Negeri Kota Pekanbaru - Rikizaputra Rikizaputra; Festiyed Festiyed; Skunda Diliarosta; Arlian Firda (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
ABSTRACTThis research aims to find out the ethnoscience knowledge profile of biology teachers at Pekanbaru City State High School and the obstacles faced by biology teachers in implementing ethnoscience in learning. This study is a survey study at Pekanbaru City State High School using google form-based questionnaires and online interviews. The research population is a biology teacher who teaches at Pekanbaru City State High School with a sample of 40% of biology teachers taken randomly simply. The data is analyzed with descriptive percentage techniques. The results showed that 27.30% of teachers knew ethnoscience concepts, 63.60% were unaware and 9.10% did not know. Ethnoscience implementation in learning is carried out by 22.70% in a planned manner, 36.40 unplanned and 40.90% never implies ethnoscience. 27.70% felt the lack of application of curriculum demands became an obstacle in ethnoscience implentation, 63.60% of teachers lacked understanding in integrating, 13.60% felt due to environmental constraints. 60% of teachers say important ethnoscience is implemented in learning, 30% is less important and 10% of teachers feel unimportant. Thus it can be concluded that in general teachers are less aware of ethnoscience concepts and never apply because they lack understanding of integrating, whereas important ethnoscience is implemented.Keywords: ethnoscience, teacher, biologyABSTRAK Penelitian ini bertujuan untuk mengetahui profil pengetahuan etnosains guru biologi di SMA Negeri se Kota Pekanbaru dan kendala yang dihadapi guru biologi dalam mengimplementasikan etnosains dalam pembelajaran. Penelitian ini merupakan penelitian survei di SMA Negeri Se Kota Pekanbaru menggunakan angket berbasis google form dan wawancara online. Populasi penelitian merupakan guru biologi yang mengajar di SMA Negeri se Kota Pekanbaru dengan sampel 40 % guru biologi yang diambil secara acakmsederhana. Data dianalisis dengan teknik deskriptif persentase. Hasil penelitian menunjukkan bahwa 27,30% guru mengetahui konsep etnosains, 63,60% kurang mengetahui dan 9,10% tidak mengetahui. Implementasi etnosains dalam pemeblajaran dilakukan oleh 22,70% secara terencana, 36,40& tidak terencana dan 40,90% tidak pernah mengimplentasikan etnosains. 27,70% merasa kurang ekplisitnya tuntutan kurikulum menjadi kendala dalam implentasi etnosains, 63,60% guru kurang paham dalam mengintegrasikan, 13,60% merasa karena kendala lingkungan. 60% guru menyatakan etnosains penting diimplementasikan dalam pembelajaran, 30% kurang penting dan 10% guru measa tidak penting. Dengan demikian dapat disimpulkan bahwa secara umum guru kurang mengetahui konsep etnosains dan tidak pernah penerapkan karena kurang paham mengintegrasikan, padahal etnosains penting diimplementasikan.Kata kunci: etnosains, guru, biologi